Psychometric properties of the parenting daily hassles in a sample of portuguese parents - Costa,Pedro Alexandre (2021)
Abstract The Parenting Daily Hassles (PDH) scale is a screening measure of hassles associated with parenting. This study evaluated the psychometric properties of the PDH scale in a community sample of 444 Portuguese parents. Exploratory and confirmatory factor analyses provided evidence of factorial validity for both Intensity and Frequency dimensions. Internal reliability was high, although convergent validity was low. The associations between Frequency of PDH and satisfaction with life and dyadic adjustment provided evidence of convergent validity, and the associations between both Frequency and Intensity and psychological distress provided evidence of divergent validity. The findings provided further support for the adequacy and validity of the PDH scale, although the Intensity dimension performed slightly better than the Frequency dimension regarding factorial validity whereas the Frequency dimension performed better than the Intensity dimension regarding convergent and divergent validities. The PDH scale is a reliable measure of parenting daily stressors despite some limitations.